2019
DOI: 10.1590/s0004-2803.201900000-17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Unsuccessful of Treatment for Fecal Incontinence Biofeedback for Fecal Incontinence in Female

Abstract: BACKGROUND: Biofeedback is an effective method of treatment for fecal incontinence but there is controversy regarding factors that may be correlated with its effectiveness. OBJECTIVE: To evaluate the efficacy of biofeedback in the treatment of fecal incontinence, identifying the predictive factors for unsuccessful treatment. METHODS: Consecutive female patients who had fecal incontinence and were treated with a full course of biofeedback were screened. The symptoms were evaluated using Cleveland Clinic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
(59 reference statements)
1
24
1
Order By: Relevance
“…61,83,122,125,141,142, 146,170,183,199,200,227,251,253,258,261,264,285,296,298,302,353 Endoanal ultrasonography was performed in 104 studies (34.0%). 53,65,72,73,7678,80,83,86,90,92,104,105,109,110,113, 115,122,125,127,133,141,142,146,151153,155,157,162,163,165,167,172176,178,179,183,191,193,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61,83,122,125,141,142, 146,170,183,199,200,227,251,253,258,261,264,285,296,298,302,353 Endoanal ultrasonography was performed in 104 studies (34.0%). 53,65,72,73,7678,80,83,86,90,92,104,105,109,110,113, 115,122,125,127,133,141,142,146,151153,155,157,162,163,165,167,172176,178,179,183,191,193,…”
Section: Resultsmentioning
confidence: 99%
“…Anal manometry was used in 126 studies (41.2%) 50 , 53 , 55 , 57 , 61 , 65 , 72 , 73 , 77 , 78 , 80 , 82 , 83 , 85 , 86 , 91 , 92 , 95 , 96 , 98 , 103–107 , 109 , 111 , 115 , 122 , 123 , 125 , 127 , 134 , 141 , 142 , 146 , 151–153 , 155 , 162–165 , 167 , 168 , 170 , 174–176 , 178 , 179 , 183 , 191 , 193 , 199–201 , 204 , 206 , 213 , 217 , 218 , 223 , 227 , 228 , 230 , 234 , 236 , 237 , 239 , 240 , 244–251 , …”
Section: Resultsmentioning
confidence: 99%
“…We have read with great interest the article "Predictors of unsuccessful of treatment for fecal incontinence biofeedback for fecal incontinence in female" by Murad-Regadas SM et al (1) . We congratulate the journal and the Authors for the publication of a paper on the indications, outcomes and modality of biofeedback treatment in patients with fecal incontinence.…”
mentioning
confidence: 99%
“…The third paper by Murad-Regadas SM (8) evaluated prospectively the outcome of biofeedback (BF) treatment for fecal incontinence.…”
mentioning
confidence: 99%
“…The study of Murad-Regadas SM et al (8) , as in the study of Terra MP et al (10) , analyzed the results of BF treatment for incontinent patients, looking for prognostic factor that my influence results. It is also suggested that a faster track might be used in the up scaling of treatment for this patients, rising the question: should bad prognoses patients be submitted to a full, time and cost consuming, BF protocol to achieve a frustrating result, in this often depressed patients, or should they start a different approach to achieve a better chance of response?…”
mentioning
confidence: 99%